Digital Module-Based Hybrid Collaborative Learning in Tennis Learning within the MBKM Framework - Septian Raibowo; Eko Risdianto; Oddie Barnanda Rizky; Hendra Jondri Hiskya; Destriani; Muhammad Soleh Fudin (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and evaluate a digital module for hybrid collaborative learning in a Lawn Tennis course within the Merdeka Belajar Kampus Merdeka (MBKM) framework. The study employed a Research and Development (R&D) design using the ADDIE model, involving 64 students from two universities selected through purposive sampling. Data were collected using expert validation sheets, observation checklists, student response questionnaires, and learning outcome tests. Data analysis combined descriptive statistics and normalized gain (N-gain) analysis, supported by comparative analysis of pre-test and post-test results to measure learning improvement. The validation results indicated that the module achieved feasibility scores above 85% across all aspects, categorized as highly feasible.The implementation showed high engagement (85–95%). The N-gain score of 0.56 (moderate category) indicates a meaningful improvement in cognitive learning outcomes, with an average score of 78 and 75% mastery. Technical performance also improved, with an average score of 80%. These findings highlight that the module effectively improves both theoretical understanding and technical skills while supporting collaborative learning within the MBKM framework.